DIGITALIZATION OF PUBLIC-PRIVATE PARTNERSHIP AS A STRATEGIC IMPERATIVE FOR ENSURING THE STATE’S ECONOMIC SECURITY: A BIBLIOMETRIC ANALYSIS AND THE EVOLUTION OF SCIENTIFIC APPROACHES - Larysa Hrytsenko; Ihor Alieksieiev; Oleksandr Hrytsenko; Vitaliy Romanchukevych; Oksana Storozhenko; Iryna Kozhushko (Financial and credit activity problems of theory and practice, 2026)
This article is devoted to the timely issues of digitization of public-private partnerships as a strategic tool for ensuring the state's economic security in the context of global instability and war threats. The relevance of the study is determined by the objective need to attract private capital for large-scale post-war economic recovery amidst a critical shortage of budgetary resources. In turn, securing a sufficient level of private investment is only possible through adherence to the principles of transparency, accountability, and algorithmic trust, which is facilitated by the use of digital ecosystems and modern technological solutions. The aim of the research is to provide a comprehensive scientific justification of the role of the digitalization of public-private partnerships as a strategic imperative for strengthening the country’s economic security. The study conducted a theoretical and methodological analysis of the transformation of the partnership concept from centralized structures to modern network models such as “Digital PPP” and “4P.” Using Google Trends tools, a comparative assessment was carried out of the dynamics and geographical distribution of societal interest in public-private partnerships and digitalization. Based on information from the Scopus database, an in-depth bibliometric analysis was carried out of publication activity, sectoral structure, and the geographical distribution of research devoted to the digitalization of public-private partnerships in the context of ensuring the state’s economic security. Clustering of the scientific landscape using VOSviewer software identified three most common areas of research on the topic: the fundamental principles of public-private partnerships, the technological aspects of digitalization, and public administration and the role of the state. The study paid particular attention to a chronological analysis of the evolution of academic approaches to researching the role of digitalization in public-private partnerships. The article outlines promising aspects of digitalizing the public-private partnership system to ensure economic security and the post-war reconstruction of the state.